Neuromechanics of muscle synergies during cycling - Wakeling, J.; Horn, T. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
One remarkable property of our locomotor systems is the ability to generate co-ordinated movements across a wide range of speeds and loads. We know that the relative levels of individual muscle contractions can vary with changing speed and load (Wakeling et al. 2006), but it has not been established whether these can be incorporated by the same muscle synergies. The purpose of this study was to identify whether the muscle synergies adapt to the load and velocity of a movement task by altering the relative contributions of the synergistic muscles.